Speed control of a doubly-fed induction machine based on fuzzy adaptive. (2019) - Saidi, Abderazak; Naceri, Farid
In this paper, we are interested in the adaptive fuzzy control a technique has been studied and applied, namely adaptive fuzzy control based on theory of Lyapunov. The system based on the stability theory is used to approximate the gains ke and kdce to ensure the stability of the control in particular time, simulations results obtained by using MATLAB environment gives that the fuzzy adaptive control more robust, also it has superior dynamics performances. The results and test of robustness will be presented.